Characterization and cloning of a 58/53-kDa substrate of the insulin receptor tyrosine kinase. - Yeh, T.C.; Ogawa, W.; Danielsen, A.G.; Roth, R.A. (Journal of Biological Chemistry, 1996)
A monoclonal antibody has been produced which immunoprecipitates 58- and 53-kDa proteins which are rapidly tyrosine phosphorylated in insulin-treated cells. These proteins can also be tyrosine phosphorylated in vitro by the isolated human insulin receptor. Increased tyrosine phosphorylation of these proteins is also observed in cells expressing a transforming chicken c-Src (mutant Phe-527) and in cells with the activated tyrosine kinase domains of the Drosophila insulin receptor, human insulin-like growth factor I receptor, and human insulin receptor-related receptor. P58/53 did not appear to associate with either the GTPase activating protein of Ras (called GAP) or the phosphatidylinositol 3-kinase by either co-immunoprecipitation experiments or in Far Westerns with the SH2 domains of these two proteins. Since p58/53 did not appear, by immunoblotting, to be related to any previously described tyrosine kinase substrate such as the SH2 containing proteins SHC and the tyrosine phosphatase Syp, the protein was purified in sufficient amounts to obtain peptide sequence. This sequence was utilized to isolate a cDNA clone that encodes a previously uncharacterized 53-kDa protein which, when expressed in mammalian cells, is tyrosine phosphorylated by the insulin receptor.